Evaluation of a large-scale E-learning program on emotional regulation Tipi® for hospital workers and teachers in France during the COVID−19 pandemic - Xavier de la Tribonnière; Patrick Favennec; Marie Christine Picot; Valérie Macioce; Safa Aouinti; Pascale Clément; Marie Pommier; Luc Nicon (Preventive Medicine Reports)
Objective: The Tipi® method is a rapid emotional regulation technique, focusing on physical sensations associated with an emotion, allowing both the sensations and the emotion to subside naturally. This study aimed to evaluate the effectiveness of an e-learning program on the Tipi® method in reducing stress and negative emotions among healthcare professionals and teachers during the COVID−19 pandemic. Methods: This prospective observational study was conducted online in 2020 and 2021. The program was offered to 82,000 hospital workers and 84,000 teachers in France (members of a mutual insurance company). It consisted of two modules, with online assessments. The primary outcome was the change in stress level (on a 0–10 scale), from baseline to three months. Results: 2648 individuals registered for the program, and 456 completed the assessment questionnaire. Follow-up rates were 47 % at one month and 31 % at three months. The first module was completed by 76 % and 19 % completed both. Stress and emotions significantly decreased at one month and three months, with a median reduction of one point on a 10-point scale, considered clinically meaningful at population level. Stress decreased by 14 % at one month (p < 0.01) and three months (p < 0.01). Anxiety reductions were 14 % at one month (p < 0.01) and 17 % at three months (p < 0.01). Greater improvements were observed in those who practiced the Tipi® method. Satisfaction was moderate (e-learning, 7/10. Tipi® method 6/10). Conclusions: The Tipi® e-learning program showed feasibility, acceptability, and effectiveness in reducing stress and negative emotions among hospital workers and teachers.